PENGARUH LINGKUNGAN FISIK, PERSEPSI NILAI DAN CITRA HOTEL TERHADAP NIAT KONSUMEN MEMILIH HOTEL DI KOTA PALEMBANG - Heri Setiawan (Program Studi Magister Manajemen FE Unsri, 2016)
This study aims to determine the influence of the physical environment, perceived value, and image of hotel on consumer behavioral intentions. Population of this research is all the people who've been stay at 3 and 4 star hotels in Palembang. Based on the number of existing populations obtained amount of sample is 183 respondents. The sampling method used in this study is non probability sampling technique with a type of accidental sampling. Based on ANOVA test results F count is 82.420 and F table is 3.189 with significance 0.000 <0.05, so the regression model can be used to predict the influence of the physical environment, perceived value and image of hotel on consumer behavioral intentions to choosing hotel. Statistical analysis showed that physical environmental factors have not significant effect on consumer behavioral intentions to choosing hotel. Perceived value have significant effect on consumer behavioral intentions to choosing hotel. Image of hotel have significant effect on consumer behavioral intentions to choosing hotel. Therefore, 3 and 4 star hotels in Palembang need to pay attention to develop and maintain better physical environments so that positive perceptions of image and value can be developed to create customers’ positive behavioral intentions